Вплив зміни теплового навантаження на температуру відхідних газів котлів газомазутних ТЕЦ - Шелешей, Тетяна Вікторівна (НТУ "ХПІ", 2018)
Нагальним є пошук шляхів підвищення надійності та економічності діючих ТЕЦ шляхом вдосконалення процесів спалювання газу, зниження теплових викидів в навколишнє середовище, витрат електроенергії на власні потреби. Встановлено, що одним з основних факторів, які впливають на оптимальну температуру димових газів, є температура живильної води. Найбільш адекватною до експлуатаційних умов є квадратична залежність. При дослідженні даних графіків встановлено, що температура відхідних газів зростає з ростом теплової потужності.

The present-day state of power engineering is rather critical. In this connection, it is of great importance to search for the ways that would allow us to increase the reliability and economic efficiency of operating heat and power plants through the improvement of gas burning processes, and through a decrease in thermal emissions to the environment and in the electric power consumption for domestic needs. The objective of this research was to carry out the experimental computation investigation of a degree of influence of the thermal power on the temperature of exhaust gases of the boilers with the maintenance of the durability of gas exhaust channels. A review of the references showed that the heat utilization of flue gases allows for an increase in the fuel consumption coefficient, a decrease in unhealthy emissions and an increase in the boiler heat power with an increase in the coefficient of efficiency, and a decrease in gas and air temperature differences. It was established that one of the main factors that affect the optimal temperature of flue gases is the feed water temperature. The analysis of the boilers of a TGMP-314A type used by Kiev heat and power plant allowed us to establish a degree of the influence of operation modes on the exhaust gas temperature texh. The adequacy of derived equations and the used data was verified by the criterion R. Calculated values of the criterion are equal to R = 0.934 for the linear relationship, R = 0.924 for the power relationship and R = 0.956 for the quadratic relationship. The most adequate relationship for operation conditions is considered to be the quadratic relationship. Investigation of the given diagrams showed that the temperature of exhaust gases is increased with an increase in the thermal power by 8 °С (tfw = (230-242) °С NЕ = 163-190 MW. It is slightly increased in the range of tfw = (255-258) °C and NE = 220-250 MW from 125 °C to 133 °C and it allows us to reduce the temperature of flue gases by 18 °С on average taking into consideration the reliability of convective heating surfaces.
Influence of a change in the thermal loading on the temperature of exhaust gases of the boilers used by gas-&-fuel fired heat and power plants
Keywords: котел; змінний режим експлуатації; температура відхідних газів; електрична потужність; теплове навантаження; витрата живильної води; boiler; interchangeable operation mode; exhaust gas temperature; electric power; thermal loading; life water temperature; consumption